2011
DOI: 10.17221/1555-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of brucellosis in ruminants in Bangladesh

Abstract: ABSTRACT:The prevalence of brucellosis was determined in the ruminants (buffaloes, cattle, sheep and goats) of five different districts viz. Bagerhat, Bogra, Gaibangha, Mymensingh and Sirajgonj of Bangladesh. A total of 550 sera samples of 105 buffaloes, 188 cattle, 127 goats and 130 sheep were screened by RBT and were further confirmed with I-ELISA. A structured questionnaire was used to collect epidemiological information on the animals. The overall serological prevalence derived from the samples was 2.87% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 10 publications
10
50
9
Order By: Relevance
“…The difference between the groups was not statistically significant. In contrast to the findings of the present study, Rahman et al (2011) reported the prevalence of brucellosis in the cow aged 2.5∼4 years as 1.45 % while in the cows over four years of age as 5.31%. Similarly, Amin et al (2004) reported 2.3% and 4% prevalence in the <4 and >4 years age group, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…The difference between the groups was not statistically significant. In contrast to the findings of the present study, Rahman et al (2011) reported the prevalence of brucellosis in the cow aged 2.5∼4 years as 1.45 % while in the cows over four years of age as 5.31%. Similarly, Amin et al (2004) reported 2.3% and 4% prevalence in the <4 and >4 years age group, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Rahman et al, (2011) in goats and sheep who found highest seroprevalence of brucellosis by RBPT followed by STAT and I-ELISA. Shome et al, (2006) in sheep and goats who found lower seropositivity of 7.36% by I-ELISA as compared to 9.95% by RBPT from Rajasthan, Gujarat and Karnataka.…”
Section: Comparative Efficacy Of Serological Testsmentioning
confidence: 73%
“…No prevalence of brucellosis was recorded in buffalo both in Bogra and Gaibandha districts. Age and sex as potential risk factors for brucellosis in buffalo was analyzed by Rahman et al (2011a). Recently Rahman et al (2013a) recorded prevalence of brucellosis in 99 buffaloes sera of Bagerhat and Mymensingh using RBT, SAT, CFT, I-ELISA, genus specific and species specific real time PCR (see Figure 9 for amplification of real time PCR).…”
Section: Brucellosis In Buffalomentioning
confidence: 99%